If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(4x + -2) = -1(6x + 4) Reorder the terms: -1(-2 + 4x) = -1(6x + 4) (-2 * -1 + 4x * -1) = -1(6x + 4) (2 + -4x) = -1(6x + 4) Reorder the terms: 2 + -4x = -1(4 + 6x) 2 + -4x = (4 * -1 + 6x * -1) 2 + -4x = (-4 + -6x) Solving 2 + -4x = -4 + -6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6x' to each side of the equation. 2 + -4x + 6x = -4 + -6x + 6x Combine like terms: -4x + 6x = 2x 2 + 2x = -4 + -6x + 6x Combine like terms: -6x + 6x = 0 2 + 2x = -4 + 0 2 + 2x = -4 Add '-2' to each side of the equation. 2 + -2 + 2x = -4 + -2 Combine like terms: 2 + -2 = 0 0 + 2x = -4 + -2 2x = -4 + -2 Combine like terms: -4 + -2 = -6 2x = -6 Divide each side by '2'. x = -3 Simplifying x = -3
| 84+3x^2=x^2 | | (c-10)=-3 | | 5x+13=8x+1 | | x^2+2x+2=10 | | 6x+3+6x=-93 | | 2x-10y=44 | | 3x+14=80 | | 10-4(-8q-4)= | | 32=-18-2x | | 2(3x+7)=5(x-9) | | S=4lw+2whforL | | 2-5x=x | | factorx^2+2x-14=0 | | 120=15*2n | | 3i+5=9i+2 | | -3+6x+7x=-27 | | 2x+14=80 | | (-3x+4)=-8(x-3) | | (-3x+4)=-8x-3 | | (x+3)(x-3)=(x-5)(x-3) | | 84-3x^2=x^2 | | 4x+155=11x-6 | | 40x+12y=600 | | -6p-4(4-3p)=4(p-4)-10 | | 9r+16=5 | | 4w^2+16w+15= | | 0=ln(cos(2x)) | | 5x+4=2+4x | | 5x-2+3x=8x-2 | | 3x^3+2x^2-27x-18=x | | 50=5n*2 | | 4x^2+441x+729=0 |